2018
DOI: 10.1111/jcmm.13500
|View full text |Cite
|
Sign up to set email alerts
|

Maternal diabetes up‐regulates NOX2 and enhances myocardial ischaemia/reperfusion injury in adult offspring

Abstract: Offspring of diabetic mothers are at risk of cardiovascular diseases in adulthood. However, the underlying molecular mechanisms are not clear. We hypothesize that prenatal exposure to maternal diabetes up‐regulates myocardial NOX2 expression and enhances ischaemia/reperfusion (I/R) injury in the adult offspring. Maternal diabetes was induced in C57BL/6 mice by streptozotocin. Glucose‐tolerant adult offspring of diabetic mothers and normal controls were subjected to myocardial I/R injury. Vascular endothelial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…In cardiomyocytes, ROS production is primarily regulated by Nox2 [ 27 ] and cleared by SOD [ 28 ]. Studies have reported that increasing the expression of Nox2 can enhance ROS production and ultimately enhance myocardial ischaemia-reperfusion injury, and this finding may be related to the activation of the AKT signal pathway [ 29 ]. In our experiments, after hypoxia-reoxygenation, the ROS content in cardiomyocytes increased; the increase positively correlated with the expression of Bax, Nox2, and the rate of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In cardiomyocytes, ROS production is primarily regulated by Nox2 [ 27 ] and cleared by SOD [ 28 ]. Studies have reported that increasing the expression of Nox2 can enhance ROS production and ultimately enhance myocardial ischaemia-reperfusion injury, and this finding may be related to the activation of the AKT signal pathway [ 29 ]. In our experiments, after hypoxia-reoxygenation, the ROS content in cardiomyocytes increased; the increase positively correlated with the expression of Bax, Nox2, and the rate of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative and inflammatory stresses are among the pathophysiological changes postulated to occur in response to I/R ( Aragno et al, 2003 ; Chen et al, 2007 ; Wong and Crack, 2008 ; Granger and Kvietys, 2015 ; Kurian et al, 2016 ; Rovcanin et al, 2016 ; Gao et al, 2017 ). Thus, we examined the expression of the following proteins involved in oxidative stress and inflammation: NOX2 ( Lou et al, 2018 ; Zhang et al, 2018 ), ORP150 ( Kitano et al, 2004 ; Ye et al, 2013 ), SOD1 ( Jiang et al, 2015 ; Dibas et al, 2018 ), SOD2 ( Haines et al, 2010 ; Xu et al, 2010 ), NLRP3 ( He et al, 2017 ; Liu et al, 2018 ), NF-κβ ( Su et al, 2017 ; Ye et al, 2017 , 2018 ), and IFNγ ( Sun et al, 2016 ; Ferhat et al, 2018 ). The high expression of these proteins in the present I/R model implied that even a short period of ischemia, followed by reperfusion, played a major role in exaggerating tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…This may be in concert with baicalein’s ability to reduce ROS, leading to decreased interaction of oxidized Akt with PTEN, thereby promoting Akt activation [ 33 , 34 ]. The activated Akt can downregulate NADPH oxidase, a major source of ROS under both physiological and pathological conditions, via blocking mTOR phosphorylation thereby decreasing ROS generation [ 35 ]. This could be another likely mechanism whereby baicalein reduces ROS generation, other than the possibilities of scavenging ROS or inhibiting Fe 2+ -regulated radical production.…”
Section: Discussionmentioning
confidence: 99%